Efectos de un programa de entrenamiento físico con el empleo del balón, para el desarrollo de la fuerza explosiva y la aceleración en la categoría cadetes masculino (14 a 16 años) de la liga Quindiana de balonmano (2019)
This project aimed to determine the effects of a physical training program with the use of the ball, for the development of explosive strength and acceleration in the male cadet category (14 to 16 years) of the Quindiana handball league, the methodology of study had a quasi-experimental quantitative approach with explanatory scope, with pre-test and post test design with control group; the population was constituted by N = 20 athletes, with an age range between 14 and 16 years, the groups were distributed with the pairing technique with 10 members in each set; The experimental group was subjected to 16 sessions for 6 weeks. The variables of the explosive force and the acceleration were evaluated, by means of the long jump test without impulse and the acceleration test of 30 meters respectively. Results: it was found that there were significant differences between both tests for the experimental group both for acceleration (p = 0.005) and for explosive strength (p = 0.047) but not in the control group (p> 0.05). One of the conclusions of the study was that although the experimental group had significant increases between both tests in the two study variables, these were not statistically significant (p> 0.05) in relation to the control group in either of the two variables after the application of the training program.